A systematic study on the resistance mechanisms and degradation potential of aerobic biological systems under high-concentration nonylphenol polyoxyethylene ether stress - Xuejian Sun; Qing Qiu; Fan Wang; Ji Wu; Dejun Bian; Hongliang Huo (Journal of Environmental Sciences, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Electron Transfer Drives Preferentially Assimilatory Sulfate Reduction in Petroleum‐Contaminated Soil - Jialu Sun; Yuewei Yang; Xin Yu; Xiaolin Zhang; Pinpin Yang; Bingyang Liu; Yali Chen; Dejun Wang; Xinhong Peng; Xiaojing Li (Environmental Microbiology, 2026)
Sulfur is a vital macroelement for soil fertility and crop growth, and its bioavailability is converted with electron flux. To determine the effect of biological electron transfer on the sulfur cycle in soil, a microbial electrochemical system (MES) was established to amplify the efficiency of extracellular electron transfer. Results showed that biocurrent obviously promoted the reduction of water‐soluble SO 4 2‐ to S 2− , and afterward reoxidised to fulvic acid sulfur (FAS, 32% increment) instead of humic acid sulfur (HAS, 77% decrement). The δ 34 FAS values (12‰ to 24‰) were consistent with the typical isotopic signatures of dissimilatory sulfate reduction, while the δ 34 HAS values (−40‰ to −60‰) matched the assimilatory sulfate reduction. Meanwhile, the assimilatory SO 4 2‐ reduction to cysteine improved with a 30%–33% increase for the NAD + /NADH and secretion of cytochrome c to support robust redox. Essentially, the precursor‐product pairs of desulfonation were enhanced by 26%–93%. Compared to a 6% contribution of HAS, the formation of cysteine accounted for 55% of the electron transport flux. According to screening 32 sulfur‐transforming genes, 609 genera were identified, especially 31%–84% proliferation for Desulfatitalea . This study reveals ways of organic sulfur conversion mediated by electron transfer, which can assist the biological amendment of sulfur bioavailability in soil.

Performance enhancement mechanisms and applications of micropressure internal circulation reactors driven by flow pattern optimization - Xuejian Sun; Qing Qiu; Fan Wang; Han Li; Dejun Bian; Hongliang Huo (Process Safety and Environmental Protection, 2026)

Biomass models, allometric relationships, and carbon sink of Sargassum henslowianum in Nan'ao Island - Jing Chen; Jinhuai Ni; Hong Du; Kai Zong; Sunzhaocong Lan; Jianpeng Lu; Dejun Feng; Xu Yang; Guangyang Zhang; Lili Mei; Yuanmin Sun; Xunmeng Li (Regional Studies in Marine Science, 2026)

Hydroclimatic variability since 29 ka at Gongzhu Co, SW Qinghai-Tibet Plateau: A multi-proxy reconstruction - Haoran Tai; Mingda Wang; Tao Li; Bo Yuan; Xiaoying Chen; Xinwei Liang; Tonggang Zang; Dewen Ma; Dejun Wang; Kan Yuan; Xiaoxue Gao; Zhe Sun; et al. (Global and Planetary Change, 2026)

Ferrihydrite accelerates carbon turnover by regulating interspecific electron transfer in petroleum-contaminated soil - Xin Yu; Yuewei Yang; Jialu Sun; Pengju Zhong; Xiaolin Zhang; Jing He; Zhiwen Lin; Dejun Wang; Wenqing He; Xiaojing Li (Chemical Engineering Journal, 2026)

Neuro-tumor interactions in peripheral tumors - Xueshiyu Ma; Peixuan Ji; Jiahao Zheng; Shuqi Cai; Kan Xu; Yongwei Sun; Dejun Liu (Cancer and Metastasis Reviews, 2026)

Corrigendum to “Efficient treatment of high-strength refractory wastewater via micropressure internal circulation reactor: Performance and mechanisms” [Bioresour. Technol. 444 (2026) 133964] - Dejun Bian; Xuejian Sun; Hongliang Huo; Fan Wang; Bomin Wang; Hui Ma; Jinhao Pu (Bioresource Technology, 2026)

Efficient treatment of high-strength refractory wastewater via micropressure internal circulation reactor: Performance and mechanisms - Dejun Bian; Xuejian Sun; Hongliang Huo; Fan Wang; Bomin Wang; Hui Ma; Jinhao Pu (Bioresource Technology, 2026)

Transcriptome analysis reveals differences in postharvest fruit firmness changes between two Kiwiberry varieties - Zhao Liu; Jianyu Song; Yuying Li; Yanhong Cui; Zeyang Zheng; Kexin Zhu; Taiming Liang; Zhenpan Liu; Yang Sun; Dejun Liang (Horticulture, Environment, and Biotechnology, 2025)

Analysis of treatment effect and microbial degradation pathway of municipal wastewater by multi-stage micro pressure internal circulation mud membrane coupling process - Fan wang; Yuying Fan; Weiqing Jiang; Xuejian Sun; Ying Zhang; Songlin Liu; Dejun Bian (Journal of Environmental Chemical Engineering, 2025)

Climate change and nutrient influx disrupt karst ecosystem dynamics and tufa deposition in Huanglong, China - Muhammad Ibrar; Bing Li; Hanyong Zeng; Anđelka Plenković-Moraj; Kazimir Miculinić; Dejun An; Yanbao Lei; Geng Sun (CATENA, 2025)

Precise catalytic conversion of complex hydrocarbon molecules via “Molecular Scissors” - Shunnian Xu; Kuo Tang; Dejun Shi; Zhiguo Sun; Xiao Feng; Hongxu Gong; Gang Wang (Fuel, 2025)

Metagenomics reveals microbial community metabolic and functional changes in electroplating washing wastewater treatment systems under ultralong operating mode - Xuejian Sun; Qing Qiu; Fan Wang; Ji Wu; Dejun Bian; Hongliang Huo (Journal of Environmental Chemical Engineering, 2025)

Enhanced recovery of high-quality oil from oily sludge using solution extraction - Wenwen Di; Wenchao Lu; Li Zhang; Zhenghe Xu; Dejun Sun (Fuel, 2025)

Improvement of finescale parameterization through reducing uncertainty in spectrum estimation - Shumin Jiang; Dejun Dai; Dingqi Wang; Jia Deng; Jia Sun; Ying Li; Jingsong Guo; Fangli Qiao (Dynamics of Atmospheres and Oceans, 2025)

Linking soil extracellular enzymes with soil respiration under altered litter inputs - Hao Chen; Qianhao Xu; Kees Jan van Groenigen; Bruce A. Hungate; Pete Smith; Dejun Li; Daryl L. Moorhead; Brooke B. Osborne; Zilong Ma; Jørgen E. Olesen; Chaoqun Wang; Ji Liu; et al. (Agricultural and Forest Meteorology, 2025)

Comparative efficacy of anaerobic digestion systems in removing antimicrobial resistance genes from swine wastewater - Da Sun; Xiaomin Shi; Yingbo Shen; Ying Liu; Sunlin Luo; Yongpeng Jin; Weishuai Zhai; Lu Liu; Zhaoju Deng; Chengtao Sun; Dejun Liu; Xin Yang; et al. (Journal of Hazardous Materials, 2025)

Laboratory Investigation of the Uplift Resistance of a New Winged H-Pile Anchor Developed for Offshore Marine Aquaculture - Xu Yang; Lianghao Tang; Lili Mei; Tianyuan Zhang; Shuai Niu; Zhefei Sun; Zhenliang Wang; Dejun Feng; Fukun Gui (Journal of Marine Science and Engineering, 2025)
To enhance the stability and safety of marine aquaculture facilities by addressing the limited uplift resistance capacity and susceptibility to deflection of conventional straight-shafted piles, this study introduces an improved H-pile anchor and conducted laboratory experiments. The new anchor incorporates resized H-piles with wing plates added to both sides, optimized for area and placement, as well as an adjusted loading angle. The findings demonstrate a positive correlation between the uplift resistance capacity of the H-pile anchor and its length and width, indicating that while increased pile length significantly enhances resistance, widening has a minimal impact. Additionally, enlarging the wing plate area improves the resistance; however, efficiency (δ) decreases with the increase in the area, suggesting the existence of an optimal size. The optimal wing plate dimensions (L = 80 mm, W = 25 mm) improve uplift resistance by at least 10.6% compared to non-wing pile anchors. Furthermore, positioning the wing plates at the base of the pile anchor rather than the top enhances resistance by approximately 13.8%. Setting the anchor layout angle to 45° reduced the displacement under inclined loads. This research provides essential theoretical support and practical guidance for strengthening the safety and stability of marine aquaculture facilities.

Insight into metabolomics analysis of large yellow croaker liver (Larimichthys crocea) during packaging bag transport - Haofeng Sun; Fukun Gui; Dejun Feng; Ping Wang; Xiaoyu Qu; Shuai Niu; Guangyang Zhang (Aquaculture International, 2025)

Travertine deposition rather than tourism activity is the primary contributor to the microplastic risks in alpine karst lakes - Hanyong Zeng; Yijin Wang; Zhen Zhao; Dalin Zhu; Hongxia Xia; Yihua Wei; Peigang Kuang; Dejun An; Ke Chen; Ruilong Li; Yanbao Lei; Geng Sun (Journal of Hazardous Materials, 2024)

Correlation Between Water Erosion and Hydraulics of Slope–Gully Systems According to Check Dam Siltation Depth - Lulu Bai; Peng Shi; Zhanbin Li; Peng Li; Zhun Zhao; Jingbin Dong; Tanbao Li; Jingmei Sun; Dejun Wang (Water Resources Management, 2024)

New insights into interaction between oil and solid during hydrothermal treatment of oily sludge - Qi Li; Dejun Sun; Feng Chen; Haoran Xu; Zhenghe Xu (Journal of Hazardous Materials, 2024)

Protective Effects of Polysaccharide of Atractylodes Macrocephala Koidz against Porcine Aortic Valve Endothelial Cells Damage Induced by di (2-ethylhexyl) Phthalate - Yunfeng Liu; Zongyi Sun; Xiaoling Zhou; Haibin Wang; Miaomiao Yu; Dejun Li (Cell Biochemistry and Biophysics, 2024)

Study on the effect and regularity of plating parts cleaning wastewater by enhanced aerobic process with high-density bacterial flora - Ying Zhang; Xuejian Sun; Fan Wang; Ting Su; Siwen Yang; Shengshu Ai; Dejun Bian; Hongliang Huo (Journal of Environmental Management, 2024)

Microstructure-dependent CO2-responsive microemulsions for deep-cleaning of oil-contaminated soils - Lingfei Liu; Mingshan Zhang; Yi Lu; Gaojian Chen; Binda Lu; Lingling Ge; Zhouguang Lu; Dejun Sun; Zhenghe Xu (Chemosphere, 2024)

Synergistic mechanism of enhanced heavy oil recovery by compound flooding using 3D visualization model - Mingkun Zhai; Kang Zhou; Zezheng Sun; Dejun Wu; Qingjun Du; Jian Hou (Fuel, 2023)

Temperature and Dissolved Oxygen Lead to Behavior and Respiration Changes in Juvenile Largemouth Bass (Micropterus salmoides) during Transport - Fukun Gui; Haofeng Sun; Xiaoyu Qu; Shuai Niu; Guangyang Zhang; Dejun Feng (Fishes, 2023)
The study aimed to investigate the effects of temperature and dissolved oxygen on juvenile largemouth bass during transportation. The experiment involved four temperature groups: 20, 15, 10, and 5 °C. We analyzed the effects of acute and uniform cooling on fish behavior to determine the optimal approach for cooling. Then, we simulated transport under different temperature conditions while measuring the dissolved oxygen level and metabolic rate until all the fish died. The results showed that acute cooling significantly influenced the tail-beat frequency of fish compared with uniform cooling, while abnormal behaviors such as increased swimming, attempted jumping out of the water, and loss of balance were observed. As the transport temperature reduced, the oxygen consumption rate of fish significantly changed at 10 °C, being 2.6 times lower than at 15 °C, with values of 0.10 ± 0.02 and 0.47 ± 0.07 mg·g−1·h−1, respectively. The critical oxygen threshold (Pcrit) of fish were 1.90 ± 0.12, 1.61 ± 0.04, 1.15 ± 0.09, and 1.12 ± 0.25 mg·L−1 at 5, 10, 15, and 20 °C. In addition, below Pcrit, hypoxia-led behavior changes and oxygen consumption rate reduction were observed at every transport temperature. The findings suggest that the optimal low temperature can reduce metabolism and improve the hypoxia tolerance of juvenile largemouth bass. We recommend transporting largemouth bass at an optimal low temperature (15 °C), monitoring fish behavior, and maintaining oxygen levels above Pcrit during transport to prevent stress.

A polysaccharide NAP-3 from Naematelia aurantialba: Structural characterization and adjunctive hypoglycemic activity - Lu Sun; Jiang Jiang; Tao Jing; Dejun Hu; Jie Zhu; Yan Zeng; Yalun Pang; Dechun Huang; Shujie Cheng; Chongjiang Cao (Carbohydrate Polymers, 2023)

Effects of Lithology on Asymbiotic N2 Fixation in Subtropical Secondary Forests, Southwest China - Zhenchuan Wang; Dejun Li; Xibin Sun; Hao Chen; Kongcao Xiao; Kelin Wang (Ecosystems, 2023)

Polysaccharide of Atractylodes macrocephala Koidz(PAMK) protects against DEHP-induced apoptosis in grass carp hepatocytes - Zongyi Sun; Dejun Li; Haibin Wang; Yu Ding; Chun Zhang; Shuyue Wang; Xuejiao Wang; Bingxin Li; Danning Xu (Fish & Shellfish Immunology, 2023)

Assessing the potential of using high spatial resolution daily NDVI-time-series from planet CubeSat images for crop monitoring - Luís Guilherme Teixeira Crusiol; Liang Sun; Ruiqing Chen; Zheng Sun; Dejun Zhang; Zhongxin Chen; Deji Wuyun; Marcos Rafael Nanni; Alexandre Lima Nepomuceno; José Renato Bouças Farias (International Journal of Remote Sensing, 2021)

Assessing Drought Conditions in Cloudy Regions Using Reconstructed Land Surface Temperature - Shiqi Yang; Dejun Zhang; Liang Sun; Yongqian Wang; Yanghua Gao (Journal of Meteorological Research, 2020)

Physical information of 2705 PCR-based molecular markers and the evaluation of their potential use in wheat - Chunhua Zhao; Han Sun; Chunhui Guan; Junpeng Cui; Qianqian Zhang; Mengmeng Liu; Mengna Zhang; Qifan Guo; Yuzhu Hou; Mingjie Xiang; Xiaomin Jiang; Xiulong Luo; et al. (Journal of Genetics, 2019)

The effect characteristics of temperature on stroke mortality in Inner Mongolia and globally - Wenfang Guo; Maolin Du; Dejun Sun; Nengjun Zhao; Zhihui Hao; Rina Wu; Chao Dong; Xiaoling Sun; Chunfang Tian; Liqun Gao; Hongwei Li; Di Yu; et al. (International Journal of Biometeorology, 2019)

Air quality improvement during 2010 Asian games on blood coagulability in COPD patients - Zili Zhang; Jian Wang; Meihua Guo; Mingmei Xiong; Qipeng Zhou; Defu Li; Jiaze Shu; Wenju Lu; Dejun Sun (Environmental Science and Pollution Research, 2016)

Nocodazole increases the ERK activity to enhance MKP-1 expression which inhibits p38 activation induced by TNF-α - Xiangrui Guo; Xueying Zhang; Yajing Li; Yuanyuan Guo; Jing Wang; Yan Li; Beifen Shen; Dejun Sun; Jiyan Zhang (Molecular and Cellular Biochemistry, 2012)

Genetic Differentiation of Native Sheep Populations in East and South Asia - Rongqing Geng; Hong Chang; Lanping Wang; K. Tsunoda; Zhangping Yang; Wei Sun; Dejun Ji; Yonghong Li (Biochemical Genetics, 2007)

Seasonal and interdecadal variations of heat transport over the northern hemisphere - Sun Jilin; Xu Delong; GU Dejun (Journal of Ocean University of China, 2006)

Phylogenetic Relationships of Sheep Populations from Coastal Areas in East Asia - Shengxia Lu; Hong Chang; Lei Du; Kenji Tsunoda; Wei Sun; Zhangping Yang; Guobing Chang; Dejun Ji (Biochemical Genetics, 2005)